Survey on Application based Wireless Communication - Raj , R.S. Sidharth; Karthik, B. (International Journal of Psychosocial Rehabilitation, 2018)
In the trend of wireless communication, the growing engineers are in position to aware various technologies existing in the global application. The modules which are integrated with wireless communication for home, Industrial, medical and Industrial secured air applications and surveillances concept based survey discussed in this article.